Contextualising Fajr Sadiq: Response to Dawn Research Findings with the Sky Quality Meter (SQM) - Maskufa, Maskufa; Damanhuri, Adi; Sopa, Sopa; Hadi, Ahmad Chairul (Mazahib, 2024)
The article needs to address the problem of dawn time too early in Indonesia. To prove this, the researcher used the Sky Quality Meter (SQM) in four locations with different sky brightness levels: Labuan Bajo, Belitung, Sidoarjo, and Bogor. In addition, the article also seeks to explain the views of the government and Islamic organization using SQM. This research uses normative, astronomical, and sociological approaches. The results showed that the value of the sun's tilt during the Dawn Sadiq period was -19.30º to -13.58º. The appearance of dawn can be detected earlier in locations with high sky brightness and low light pollution, such as in Labuan Bajo (-19.30º), while in other places with opposite conditions, the appearance of Dawn Sadiq is slower, such as in Bogor (-13.58º). If the SQM observation in Labuan Bajo is used as a reference, it will not significantly impact the current dawn schedule (dip = -20⁰). The use of SQM for dawn observation is acceptable to the Ministry of Religion and Islamic organizations. However, considering the mixed results of dawn research with SQM, the response of the Ministry of Religious Affairs, Nahdlatul Ulama, and the Islamic Association still uses dip = -20º, while Muhammadiyah shifts to dip = -18⁰. To minimize differences, it is necessary to conduct joint research on an ongoing basis to produce stable data on the setting of the sun at dawn.